Metagenomics of wheat rhizosphere for abiotic stress management - Ahlawat, Om Parkash; Tiwari, Ratan; Singh, Gyanendra Pratap (Journal of Cereal Research, 2018)
Plant microbiome also known as it’s second or extended genome, regulates and influences plant’s metabolism and growth. The plant microbiome members promote nutrient uptake, tolerance against abiotic and biotic stresses and regulate the host immune system. Although there is plenty of information available on the role of rhizosphere microbiome for plant growth, still there is a dearth of knowledge for the vast majority of rhizosphere microorganisms. This is mainly due to their unknown growth requirements or inability to grow on any known growth media. To support plant growth under stress conditions, the information on the presence of a specific microorganism in rhizosphere microbiome along with the role it plays is very much essential. Here, we review the generalized role of plant microbiome in different plant functions, information generated till date specifically on wheat metagenomics, the role of rhizosphere microorganisms in abiotic stress management in other crop plants and the breeding in wheat in light with wheat metagenomics or metagenome engineering through breeding. DOI:10.25174/2249-4065/2018/79291